Who Among White Collar Workers Has an Opportunity for Phased Retirement? : Establishment Characteristics - Karen Grace-Martin; Robert M. Hutchens (Institute for the Study of Labor (IZA), 2004)
Utilizing a new survey of employers, this paper examines how and why establishments differ in their willingness to permit an older full-time white-collar worker to take phased retirement. Phased retirement means that an older worker remains with his or her employer while gradually reducing work hours and effort. Although older workers often express an interest in phased retirement, actual occurrences are evidently rare. A possible explanation is that employers limit opportunities for phased retirement. The survey indicates that employers are often willing to permit phased retirement, but primarily as an informal arrangement. The results also indicate that opportunities for phased retirement are greater in establishments that employ part-time white-collar workers, allow job sharing, and have flexible starting times. Opportunities tend to be more limited in establishments where white collar workers are unionized, and where the establishment is part of a larger organization.
Keywords: J14; J26; 330; retirement; employer surveys; older workers; multiple imputation; Flexible Altersgrenze; Angestellte; Betriebsgrösse; Schätzung; Vereinigte Staaten